Prosedur dan Efektifitas Mekanisme Penyelesaian Sengketa Perdagangan dan Investasi Dalam ASEAN - Mauldiansyah, Fariz (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Trade and investment play an important role in the practice of relations between countries in the prospective economic cooperation efforts to increase the economic growth of each country. In this regard, ASEAN also has legal instruments that regulate transactions and investments among other countries. In the trade regime, ASEAN has several agreements such as the ASEAN Free Trade Agreement, ASEAN Trade in Goods Agreement, ASEAN Trade in Services Agreement, ASEAN Framework Agreement on Services, and so on. Meanwhile in the investment regime, ASEAN has the ASEAN Comprehensive Investment Agreement. One of the important components in a Regional Trade Agreement is the clause of a legally binding dispute settlement mechanism. In the trade regime, the system and mechanism of the dispute resolution procedures are separated from other trade agreements, the ASEAN Protocol on the Enhanced Dispute Resolution Mechanism. Meanwhile in the Investment regime, the system and mechanism of the dispute resolution procedure are regulated in the same agreement in the ASEAN Comprehensive Investment Agreement. This article will describe the procedural mechanism for the dispute resolution framework of the trade and investment regime in ASEAN, as well as focus on each dispute resolution system with the preferences of each participating country, with differences in the use of the dispute system in the WTO.